Sosialisasi pendidikan karakter anak era digital bagi guru dan wali murid MIM Tegalampel, Klaten - Choirun Nisa; Muhamad Taufik Hidayat (Tintamas: Jurnal Pengabdian Indonesia Emas, 2026)
The rapid expansion of digital technology has increased children's exposure to smartphones, the internet, and digital media, creating both learning opportunities and risks, including harmful content, internet addiction, cyberbullying, and reduced family interaction. This community service program aimed to strengthen parents' understanding of digital parenting to support children's character development in the digital era. The program was conducted on September 10, 2025, at Tegalaampel Village Hall and involved 113 parents and guardians of students from MIM Tegalaampel. The intervention consisted of a parenting seminar and interactive discussions covering digital literacy, family communication, guidelines for managing children's screen time and digital content, gadget-free quality time, positive discipline through rewards and consequences, and strengthened collaboration between families and schools. The program improved participants' understanding of effective digital parenting practices and strategies for managing children's technology use while fostering positive character development. These findings suggest that enhancing parental capacity through digital parenting education and sustained family–school collaboration provides an effective approach to strengthening children's character in the digital age.